PARA UNA INTERPRETACION EPISTEMOLOGICA DE LA GEOGRAFÍA A PARTIR DE LA DIALÉCTICA (for an epistemologic interpretation of geography from dialectic) - Rodriguez, José Mateo; Silva, Edson Vicente da (Mercator, 2008)
El trabajo está dedicado a presentar las características de la Geografía fundamentada en una perspectiva del materialismo dialéctico. Se presenta un esbozo histórico de los antecedentes originados en los planteamientos de los naturalistas materialistas espontáneos, dándose un destaque a las características de la Geografía Marxista elaborada en la Unión Soviética. Se numeran los elementos básicos del pensamiento dialéctico, y se realiza una caracterización del mismo en la esfera de la interacción entre la naturaleza y la sociedad. Atención particular se le presta a analizar la concepción sistémica desde una perspectiva dialéctica. Parte significativa del trabajo se le da a los fundamentos metodológicos, teóricos, institucionales y aplicativos de una Geografía formulada desde una perspectiva dialéctica. Se aclaran cuestiones tales como el objeto de estudio, las categorías geográficas, la estructura de las ciencias geográficas y los diferentes niveles de aplicabilidad. Por último, se plante la importancia que tiene para la Geografía y la ciencia en general, el incorporar el pensamiento dialéctico, en el momento actual de reformulación epistemológica de las disciplinas científicas. Palabras llaves : Geografía, Dialéctica, Sistemas, Naturaleza, Sociedad. ABSTRACT The work is dedicated to present the characteristics of the Geography based in a perspective of the dialectical materialism. Is presented a historical sketch of the antecedents originated in the positions of the spontaneous materialistic naturalists, being given an it highlights to the characteristics of the Marxist Geography elaborated in the Soviet Union. The basic elements of the dialectical thought are numbered, and is carried out a characterization of the same one in the sphere of the interaction between the Nature and the Society. Particular attention is gave to analyze the systemic conception from a dialectical perspective. It leaves significant of the work that is given to the methodological, theoretical, institutional foundations and applications of a Geography formulated from a dialectic perspective. They clear up such questions as the study object, the geographical categories, the structure of the geographical sciences and the different levels of applicability. Lastly, the importance is planted that has for the Geography and the science in general, incorporating the dialectical thought, in the current moment of epistemological reformulation e of the scientific disciplines. Key Words : Geography, Dialectics, Systems, Nature, Society.